Radiological Diagnosis of a Rare Premature Aging Genetic Disorder: Progeria (Hutchinson-Gilford Syndrome) - Haji Mohammed Nazir; Akshiitha Ramesh Baabhu; Yuvaraj Muralidharan; Seena Cheppala Rajan (Case Reports in Radiology)
Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare disease with a combination of short stature, bone abnormalities, premature ageing, and skin changes. Though the physical appearance of these patients is characteristic, there is little emphasis on the characteristic radiological features. In this paper, we report a 16-year-old boy with clinical and radiological features of this rare genetic disorder. He had a characteristic facial appearance with a large head, large eyes, thin nose with beaked tip, small chin, protruding ears, prominent scalp veins, and absence of hair.